Effect of novel cryotherapy method on frequency spectrum of lower limb muscles during running and walking - Alipour Sarinasirloo, M.; Siahkouhian, M.; Jafarnezhadgero, A.; Rahmanpour, A. H. (Journal of Advanced Sport Technology, 2020)
Cryotherapy is one of the important factors in changing muscular function. The purpose of the present study was to investigate the effect of using novel cryotherapy method on frequency spectrum of lower limb muscles during running and walking before and after muscular fatigue.This study was quasi-experimental. Ten male novice soccer players volunteered to participate in this study. A wireless electromyography system with 8 pairs of surface electrodes was used to record the electromyography activity before and after muscular fatigue in temperature of 8 and 11 º C during walking and running. During walking, frequency spectrum of rectus femoris muscle after fatigue at 11 ° C was greater than before fatigue by 16.43% (p=0.047). Frequency spectrum of semi-tendentious muscle after fatigue at 11 ° C was higher than before fatigue by 38.11% (p=0.044). In addition, frequency spectrum of rectus femoris muscle after fatigue at 8 ° C was higher than before fatigue during running by 28.56% (p=0.031). Cryotherapy increased the frequency spectrum at 11 ° C in the semi-tendentious and rectus femoris muscles during walking and increased the frequency spectrum at 8 ° C in the rectus femoris muscle during running. It seems that using cryotherapy after fatigue may improve muscle function during different activities.